Conjugated linoleic acid and oxidative behaviour in cancer cells. (May 2001) - Devery, R.; Miller, A.; Stanton, C.
Abstract : Convincing evidence from rodent models of carcinogenesis indicates that cis -9, trans -11 (c9t11) conjugated linoleic acid (CLA) is a potent naturally occurring anti-carcinogen in the human diet. CLA has been reported to alter the fatty acid composition of biological tissues in a manner that increases their oxidative stability. However, recent information suggests that an antioxidant role for CLA does not seem plausible. Given the knowledge that c9t11 CLA is present in a wide range of meat and dairy food products, our studies have begun to investigate mechanisms by which CLA-enriched milk fat exerts its anti-carcinogenic effects. An oxidative mechanism appears to be involved in its growth-suppressive effects, since supplementation of growth culture medium with CLA (17–71.5 μM) made breast cancer cells more susceptible to lipid peroxidation. Studies have indicated that cancer cells may become enriched in CLA during growth in culture. This may make intracellular lipids more susceptible to ordinary levels of oxidative stress, to the point of producing a cytotoxic effect.